2021
DOI: 10.21608/asejaiqjsae.2021.199393
|View full text |Cite
|
Sign up to set email alerts
|

Biological Performance of Certain Bio-Agents, Fluopyram and Fosthiazate against Meloidogyne spp. on Guava Trees (Psidium guajava L.)

Abstract: In this study, the potential of some bio-agents, fluopyram and fosthiazate were investigated against rootknot nematodes (Meloidogyne spp.) on guava trees under field conditions for two successive seasons (2020 & 2021). The examined bio-agents were; Bio-Nematon ® (Paecilomyces lilacinus), Bio Cure-F ® (Trichoderma viridi), Bio Cure-B ® (Pseudomonas fluorescens) and BIOTECT ® (Bacillus thuringiensis var. kurstaki). The infection parameters of root-knot nematodes (Meloidogyne spp.) were recorded at 35 and 70 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…In a recent study in Egypt, fluopyram (Velum prime ® 40% SC) which is a new registered nematicide found to be effective against the root-knot nematodes (Meloidogyne spp.) compared with biocontrol agents on guava trees under field conditions (Massoud et al, 2021). The obtained results showed that fluopyram significantly reduced the soil population, galls and eggs ranged from 71.75 to 77.85%, 57.90 to 62.84% and 67.13 to 88.45%, respectively.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In a recent study in Egypt, fluopyram (Velum prime ® 40% SC) which is a new registered nematicide found to be effective against the root-knot nematodes (Meloidogyne spp.) compared with biocontrol agents on guava trees under field conditions (Massoud et al, 2021). The obtained results showed that fluopyram significantly reduced the soil population, galls and eggs ranged from 71.75 to 77.85%, 57.90 to 62.84% and 67.13 to 88.45%, respectively.…”
Section: Discussionmentioning
confidence: 96%
“…The abundance of Trichoderma species in soil are form protective barriers from root pathogens (Nederhoff, 2001). The nematicidal effect of Trichoderma album has been described by several authors (Massoud et al, 2021;Raddy et al, 2013 andRadwan et al, 2011).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Nematicides are chemicals employed in various agricultural practices to control plant parasitic nematodes. Farmers are preferred to use non-fumigant nematicides, especially traditional nematicides 8 . The available choices to manage plant parasitic nematodes are limited.…”
Section: Introductionmentioning
confidence: 99%